1996
DOI: 10.1074/jbc.271.13.7445
|View full text |Cite
|
Sign up to set email alerts
|

Active Human Cytomegalovirus Protease Is a Dimer

Abstract: The quaternary state of the human cytomegalovirus (hCMV) protease has been analyzed in relation to its catalysis of peptide hydrolysis. Based on results obtained from steady state kinetics, size exclusion chromatography, and velocity sedimentation, the hCMV protease exists in a monomer-dimer equilibrium. Dimerization of the protease is enhanced by the presence of glycerol and high concentrations of enzyme. Isolation of monomeric and dimeric species eluted from a size exclusion column, followed by immediate ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
149
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(170 citation statements)
references
References 13 publications
21
149
0
Order By: Relevance
“…The dilution method has been used to study the dimer-monomer equilibrium of several herpes viral proteases with K d values in the nanomolar range (33)(34)(35). If the monomeric DPP-IV has a very low activity as observed for monomeric H750A and H750E, dilution of the protease to a concentration near or below the K d value might result in the formation of low activity monomeric DPP-IV.…”
Section: Fig 5 Sedimentation Velocity Analysis Of Dpp-iv Proteinsmentioning
confidence: 99%
“…The dilution method has been used to study the dimer-monomer equilibrium of several herpes viral proteases with K d values in the nanomolar range (33)(34)(35). If the monomeric DPP-IV has a very low activity as observed for monomeric H750A and H750E, dilution of the protease to a concentration near or below the K d value might result in the formation of low activity monomeric DPP-IV.…”
Section: Fig 5 Sedimentation Velocity Analysis Of Dpp-iv Proteinsmentioning
confidence: 99%
“…A central part of the regulation of assemblin activity is a monomer-dimer equilibrium [37]. The dimer is weakly associated with dissociation constants (K D ) in the micromolar range [79].…”
Section: Regulation Of Activitymentioning
confidence: 99%
“…It is the active species, while the monomer is almost inactive. The equilibrium is shifted towards the dimer by higher concentrations of assemblin, salts and co-solvents like glycerol [37,75,79]. Dimerization induces refolding of a loop (residues 162 to 171) near the active site.…”
Section: Regulation Of Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lightscattering studies showed that the protease was monodisperse in solution and existed as dimers. This observation was made before the appearances of published reports showing the presence of the dimer and suggesting that the dimer is the active form of the enzyme (Darke et al, 1996;Margosiak, Vanderpool, Sisson, Pinko & Kan, 1996). Initial crystallization conditions were found with the sparse-matrix sampling technique (Jancarik & Kim, 1991), using a commercial kit (Hampton Research).…”
Section: Treatment Of Crystalsmentioning
confidence: 99%